Diversity and Distribution of Bats in Triyuga and Chaudandi Municipality, Udayapur, Nepal (ZOO-Journal, 2021)
Eastern Nepal is rich in bats diversity, 34 species of bats have been recorded from 11 eastern districts and three districts remain till now. Even most of the districts surveyed including Udayapur have been focused only at some sites. Most of the area in the previously surveyed district has yet to be conducted. There is a lack of public awareness of the importance and values of bats. Many people have a negative attitude towards bats and there exist some prevailing threats to bats in Nepal. Study area includes 17 sites Churia range and Inner-Terai of Udayapur district. Roost survey and mist netting were conducted during six days of 2015 and 2016. In total four species of bats were recorded. 14 individuals of bats were captured from the roosts by gloved hands. However, bat could not be captured in mist nets. Previously, bat surveys were conducted at Katari in Udayapur District. Pipistrellus sp. from 12 sites, Cynopterus sphinx from three sites, Megaderma lyra from two sites Taphozous longimanus was recorded from one site. Similar, most of the people had no idea on the importance and value of bats. No direct threats on bats were observed in the study area during the survey.